Seismic monitoring of a small CO2 injection using a multi-well DAS array: Operations and initial results of Stage 3 of the CO2CRC Otway project. (September 2021) - Pevzner, Roman; Isaenkov, Roman; Yavuz, Sinem; Yurikov, Alexey; Tertyshnikov, Konstantin; Shashkin, Pavel; Gurevich, Boris; Correa, Julia; Glubokovskikh, Stanislav; Wood, Todd; Freifeld, Barry; Barraclough, Paul
Abstract: Active time-lapse seismic is widely employed for monitoring CO2 geosequestration due to its ability to track the distribution of fluids in space and time. However, standard 4D seismic monitoring suffers from several challenges, including high cost, disruption to other land uses, and, consequently, relatively large intervals between monitor surveys. Some of these challenges can be mitigated using permanently installed sources and receivers. Such an approach was tested at the CO2CRC Otway site by continuous offset VSP monitoring of 15, 000 t of supercritical CO2 injected into an aquifer 1, 500 m deep with nine permanent seismic sources (surface orbital vibrators or SOVs) and five downhole fibre-optic receivers. This continuous monitoring is complemented by multi-well 4D VSP using a mobile vibroseis source and the same DAS receivers, which included one baseline and two monitor surveys after injection of 4, 000 and 12, 000 t of CO2 . The continuous DAS-SOV monitoring detected an abrupt increase of travel times below the injection interval on the second day of injection (after injection of 300 t of CO2 ) and tracked the growth of the areal CO2 plume by mapping changes of reflection amplitudes. The plume is also detected by time-lapse changes of reflection amplitudes in multi-well 4D VSPs. The plume images obtained from continuous offset VSP and 4D VSP are broadly consistent with each other but with some differences due to differences in illumination, lateral variations of velocities and seismic anisotropy. These differences also serve as a measure of uncertainty of 4D VSP images.